223 EVALUATION OF MITOGENIC STIMULATION IN STEADY-STATE SICKLE CELL DISEASE PATIENTS. Issue 1 (1st January 2007) - Scavella, A.; Monjure, H.; Zea, A.; Leiva, L.; Gardner, R.
Abstract : Purpose of Study: Some, but not all, of causes of immune dysfunction in sickle cell disease (SSD) are well established. l-Arginine (Arg), an important factor in cellular/humoral immunity, is deficient in SSD. We investigated a possible causal relationship between Arg deficiency in SSD and immune dysfunction. Mitogenesis in SSD in steady state with and without Arg supplementation was measured. Methods: Eight steady-state (no vaso-occlusive episodes, immunosuppressants, fever/infection, or transfusions) SSD patients at Children's Hospital of New Orleans were studied. Seven controls (not all age-matched) were used. Peripheral blood mononuclear cells were isolated by Ficoll centrifugation, cultured at 37°C with a final concentration of 10 5 cells/mL in RPMI-1640 having no Arg or glutamine and 40% autologous plasma or fetal calf serum (FCS). Arg and PHA were later added. Cells were cultured in triplicate. Cells were pulsed with 3 H thymidine and the isotopes's incorporation measured. Summary of Results: FCS resulted in high background, so autologous plasma was used in subsequent experiments. Results are shown in the following graph as means ± SEM: Conclusion: Both patient and control cells showed increased levels of mitogenic response after addition of Arg, with the response in the patient group being much greater. Because of low N, the changes were not significant. The greater than normal mitogenesis in SSD with/without Arg appears to support the statement that SSD is a chronic inflammatory state and also suggests that Arg supplementation may benefit these patients by enhancing immune responsiveness.